Pengaruh Disiplin Kerja, Kompetensi dan Motivasi Terhadap Kinerja Pegawai Badan Penanggulangan Bencana Daerah Provinsi Sumatera Selatan - Angga Saputra; sri Rahayu; Choiriyah Choiriyah (Jurnal Bisnis, Manajemen, dan Ekonomi, 2023)
The purpose of this study is to determine the effect of work discipline, competence and motivation on employee performance of the Regional Disaster Management Agency of South Sumatra Province. A population of 150 employees was used in the research utilizing the associative approach, and 97 employees responded using a random sampling-based calculation on the Isaac and Michael formulas. The analysis technique uses the Instrument Validity and Reliability Test, the Classical Assumption Test and Multiple Linear Regression using SPSS 25 program. Based on the research results, known that Work Discipline has no significant effect on Employee Performance, Competence and Motivation have a significant effect on Employee Performance partially, while at the same time independent variables can explain the dependent variable of 65.1% while the remaining 34.9% is explained by the variable outside the model not included in this study